Registration of 'Spur' Hard Red Winter Wheat. Issue 2 (8th March 2018) - Berg, J. E.; Hofer, P. J.; Kephart, K. D.; Stougaard, R. N.; Lamb, P. F.; Miller, J. H.; Wichman, D. M.; Eckhoff, J. L.; Eberle, C. A.; Nash, D. L.; Holen, D. L.; Cook, J. P.; et al.
Abstract : 'Spur' (Reg. No. CV‐1139, PI 683537) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station (MAES) and licensed to the Crop Research Foundation of Wyoming in 2016. Spur was derived from the cross, MT02113*4/MTS0359. MT02113 ('Karl 92'/UT190) and MTS0359 ('Rampart'/'Mironovskaya 61') are unreleased breeding lines developed by the MAES. Spur resulted from a marker‐assisted backcross program for stem solidness and was selected as a solid‐stem F4 headrow. Spur was tested under the experimental number MTS1024 in Montana yield trials from 2010 to 2014 and in Wyoming from 2014 to 2016. Spur is a high‐yielding, semidwarf hard red winter wheat cultivar with intermediate stem solidness, medium to late maturity, and acceptable milling and baking quality characteristics. Spur's semisolid stem provides some host‐plant resistance to wheat stem sawfly.